STRATEGI KOMUNIKASI PEMASARAN CAFE SOCIAL BARN DALAM MENINGKATKAN MINAT PENGUNJUNG DI MASA PANDEMI COVID 19 - Ainaya, Andi Sapna; Kahar, Kahar; Muchtar, Sitti Murniati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2023)
The objectives of this study are: (1) To find out the Marketing Communication Strategy of Cafe Social Barn during the Covid 19 Pandemic; (2) To find out the Factors influencing Cafe Social Barn's marketing communication strategy. This research lasted approximately 6 months (May 2022 - November 2022) in Makassar City. This research uses descriptive qualitative research methods. Informants are determined using purposive sampling techniques based on certain criteria that have relevance to the purpose of the study. The primary data of the study was sourced from interviews with the owner of Cafe Social Barn and the admin of Cafe Social Barn. Secondary data is sourced from books, journals, and previous research and other materials that support the research. Data collection techniques use nonparticipant observation methods, in-depth interviews, and literature studies. Data analysis techniques use Miles and Huberman analysis models. The results of this study reveal that Cafe Social Barn's marketing communication strategy, namely the 4P marketing mix strategy, helps increase the interest of Cafe Social Barn visitors. The Marketing Communication Strategy implemented by Cafe Social Barn includes (1) Product Strategy that prioritizes Quality, Visual, and Service indicators provided to consumers. (2) Price Strategy, which is to add up the cost of product raw materials, the cost of maintaining the premises, and the profits you want to get. (3) The Place Strategy prioritizes indicators of access, visibility, parking lots, environment, and government regulations. (4) The Promotion Strategy carried out by Social Barn, namely advertising and sales promotion, namely by placing advertisements on Instagram and Facebook and applying several product discounts. The factors that influence Cafe Social Barn's marketing communication strategy consist of inhibiting factors and supporting factors.